2015
DOI: 10.1111/pde.12654
|View full text |Cite
|
Sign up to set email alerts
|

Imiquimod and Photodynamic Therapy Are Useful in the Treatment of Porokeratosis in Children with Bone Marrow Transplantation

Abstract: Porokeratosis is an uncommon disorder that affects keratinization. Immunosuppression may favor the development of porokeratotic lesions. Patients who receive allogenic transplants represent a therapeutic challenge to dermatologists. We report two cases of porokeratosis in children with bone marrow transplant and their excellent response to imiquimod and photodynamic therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 6 publications
0
14
0
Order By: Relevance
“…found that psoriatic lesions showed some evident clinical improvement during the ALA-PDT treatment period which was reflected in a statistically significant decrease in the clinical plaque severity score 11 . Several cases of classic porokeratosis such as porokeratosis of Mibelli treated with PDT successfully revealed 9 10 . Above clinical results indicate ALA-PDT regulates keratinization, however still need specific models to confirm it.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…found that psoriatic lesions showed some evident clinical improvement during the ALA-PDT treatment period which was reflected in a statistically significant decrease in the clinical plaque severity score 11 . Several cases of classic porokeratosis such as porokeratosis of Mibelli treated with PDT successfully revealed 9 10 . Above clinical results indicate ALA-PDT regulates keratinization, however still need specific models to confirm it.…”
Section: Discussionmentioning
confidence: 99%
“…The follicular obstruction in non-inflammatory acne lesions was believed to be reduced by ALA-PDT through changing keratinocyte shedding and hyperkeratosis 2 . Recently, ALA-PDT was also shown successfully treated abnormal keratinization related dermatoses such as psoriasis and porokeratosis 9 10 11 . These clinical results suggest ALA-PDT may regulate in abnormal keratinocyte differentiation and proliferation.…”
mentioning
confidence: 99%
“…Treatment is challenging, but options include cryotherapy, carbon dioxide laser, keratolytics, 5‐flurouracil cream, vitamin D analogs, and oral retinoids. A case report recently noted good efficacy with imiquimod or photodynamic therapy in children after bone marrow transplantation . Our patient opted to pursue no treatment since the lesions were asymptomatic and he disliked applying creams.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, Gracia‐Cazaña et al . reported the successful use of MAL‐PDT to treat porokeratoses on the neck and leg of a 12‐year‐old boy, previously diagnosed with acute B‐ALL which necessitated a bone marrow transplant. Prior to PDT, lesions failed to respond to calcipotriol, 5‐FU, and 5% imiquimod.…”
Section: Methodsmentioning
confidence: 99%
“…While recurrence was observed 11 months later, the initial cosmetic response was excellent, resulting in near-complete resolution. Finally, Gracia-Cazaña et al (46) reported the successful use of MAL-PDT to treat porokeratoses on the neck and leg of a 12-year-old boy, previously diagnosed with acute B-ALL which necessitated a bone marrow transplant. Prior to PDT, lesions failed to respond to calcipotriol, 5-FU, and 5% imiquimod.…”
Section: Linear Porokeratosismentioning
confidence: 99%